Progress in the role of nanoparticles in the diagnosis and treatment of bone and joint tuberculosis - Ding, Yitong; Li, Baiyun; Yi, Yangfei; Liu, Can; Wen, Jie; Jian, Xiaohong; Li, Yufei (Frontiers in Medicine, 2025)
Bone and joint tuberculosis (BJTB), caused by Mycobacterium tuberculosis (MTB), is a prevalent form of extrapulmonary tuberculosis that poses significant challenges to global public health due to difficulties in early diagnosis, prolonged treatment cycles, and drug resistance. Recent advancements in nanotechnology have introduced novel solutions for the early detection and precise treatment of BJTB, leveraging unique physicochemical properties such as high specific surface area, targeted delivery capabilities, sustained drug release, and excellent biocompatibility. In diagnostic applications, nanomaterials markedly enhance the sensitivity and accuracy of detection methods while reducing testing time. These technologies are adaptable to resource-limited settings, enabling earlier patient intervention and mitigating disease progression risk. In therapeutic applications, nanomaterials prolong drug retention in bone tissue through targeted delivery, thereby decreasing medication frequency and minimizing toxic side effects, which significantly improves treatment efficacy. Despite substantial progress, further research is required to address long-term safety concerns, broaden clinical applicability, and evaluate performance under complex pathological conditions. This review summarizes recent advancements in nanomaterials for diagnosing and treating BJTB and identifies key areas for future research, laying the groundwork for advancing precision medicine and personalized treatments.